1984
DOI: 10.1177/089686088400400413
|View full text |Cite
|
Sign up to set email alerts
|

Does Hypercoagulability Exist in CAPD Patients?

Abstract: Blood levels of fibrinogen degradation products (FDP), factor VIII (antigen and coagulant), plasminogen and antithrombin III, as well as fibrinogen half-life were studied in 15 patients on CAPD from 3–24 months; the daily loss of these factors in the dialysate was also determined. Fibrinogen and factor VIII levels were above (p < 0.05), fibrinogen half-life was below (p < 0.05) and AT III was within the normal range. The average daily protein loss in the dialysate was 7.74: t 2.42 g; fibrinogen loss was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1989
1989
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Our data indicate that increased PS exposure in uremic platelets is associated with increased procoagulant activity by those cells, as shown by their ability to support increased generation of thrombin. Thus, loss of membrane phospholipid asymmetry with PS externalization may represent a pathogenic mechanism linking platelets to the thrombotic tendency described in dialysis patients [27–29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our data indicate that increased PS exposure in uremic platelets is associated with increased procoagulant activity by those cells, as shown by their ability to support increased generation of thrombin. Thus, loss of membrane phospholipid asymmetry with PS externalization may represent a pathogenic mechanism linking platelets to the thrombotic tendency described in dialysis patients [27–29].…”
Section: Discussionmentioning
confidence: 99%
“…Though the consequences of chronic platelet activation in uremia remain to be definitely established, activated platelets may be involved in biological reactions of potential pathophysiologic significance [24–26]. Further, since alterations in the platelet reactivity state enable these activated cells to participate actively in the thrombotic process [10], activated platelets might contribute to the thrombophilic tendency of uremia [27–29], which is at present a major problem in dialysis patients [30,31].…”
Section: Introductionmentioning
confidence: 99%
“…The etiology of increased thrombosis risk associated with PD is not clear. It is hypothesized that long‐term PD creates a hypercoagulable state similar to what is observed in nephrotic syndrome (14). Studies have identified an imbalance of procoagulant and fibrinolytic proteins in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have identified an imbalance of procoagulant and fibrinolytic proteins in these patients. Among adult PD patients, Bertoli demonstrated evidence of accelerated fibrinolysis including increased concentrations of fibrinogen, fibrin degradation products, as well as a shorter fibrinogen half‐life (14). In addition, the loss of albumin into the dialysate leading to an increased synthesis of albumin, may contribute to increased synthesis of certain coagulation factors as seen in nephrotic syndrome (15).…”
Section: Discussionmentioning
confidence: 99%
“…Hypercoagulability state has been reported to occur in patients with continuous ambulatory peritoneal dialysis (PD) by a mechanism resembling that of the nephrotic syndrome due to transperitoneal protein loss (87). Kobayashi et al have found that PD patients have significantly higher levels of blood coagulation factors (e.g.…”
Section: Pre-transplant Dialysis Modalitymentioning
confidence: 99%